2020
DOI: 10.4025/actasciagron.v42i1.42809
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of forage legumes under moderate salinity with exogenous salicylic acid or spermidine

Abstract: The present study aims to determine whether exogenous salicylic acid (SA) or spermidine (Spd) has any protective effect against salt stress. Seeds were subjected to 0, 20, 40, and 60 mM NaCl with or without salicylic acid or spermidine (0.5 mM) for 10 days. The evaluated variables were germination rate, shoot and root dry masses, glycine betaine content, lipid peroxidation, and the activities of superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX). The data were subjected to Tukey’s test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…After this concentration, E decreased, reaching its minimum value in the plants under the SA concentration of 3.6 mM (2.447 mol H 2 O m -2 s -1 ). Adequate concentrations of SA improve the physiological performance of 'All Big' bell pepper, as this compound acts by activating the antioxidant system, reducing oxidative stress and causing the leaching of ions from membranes (Pizolato et al, 2020). In a study investigating the effect of SA application on pepper plants under salinity, Kaya, Ashraf, Alyemeni and Ahmad (2020) concluded that SA is capable of reversing the negative effects of salinity on the plants, because the disturbances caused to the physiological activities in plants under salt stress can be reversed by the external supply of adequate concentrations of SA, which is able to prevent the destructive effect of ROS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After this concentration, E decreased, reaching its minimum value in the plants under the SA concentration of 3.6 mM (2.447 mol H 2 O m -2 s -1 ). Adequate concentrations of SA improve the physiological performance of 'All Big' bell pepper, as this compound acts by activating the antioxidant system, reducing oxidative stress and causing the leaching of ions from membranes (Pizolato et al, 2020). In a study investigating the effect of SA application on pepper plants under salinity, Kaya, Ashraf, Alyemeni and Ahmad (2020) concluded that SA is capable of reversing the negative effects of salinity on the plants, because the disturbances caused to the physiological activities in plants under salt stress can be reversed by the external supply of adequate concentrations of SA, which is able to prevent the destructive effect of ROS.…”
Section: Resultsmentioning
confidence: 99%
“…Several strategies, including physicochemical treatment methods, have been applied to increase the tolerance of plants to salinity, e.g., exogenous application of salicylic acid (SA) (Karlidag, Yildirim, & Turan, 2009;Nazar, Umar, Khan, & Sareer, 2015;Farhadi & Ghassemi-Golezani, 2020;Pizolato et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Leaf area (LA) had a greater relationship with the no-stress control, leaf area ratio (LAR) had a greater relation with Spd and Spm in moderate salt stress, and specific leaf area (SLA) had a greater relation with Put and moderate salt stress (Figure 6). The decrease in cell growth processes is caused by dehydration that resulted from the osmotic effect of salts that accumulated in the root area and the toxic effect of Na + and Cl − , which accumulated in plant tissues and impaired physiological processes and cell membrane integrity (Pizolato Neto et al, 2020). Plants under stress that are treated with Spd and Spm have increased dry mass compared with tomatoes grown without treatment (Lycopersicon esculentum Mill.)…”
Section: Resultsmentioning
confidence: 99%